Forces and motion - Lafferty, Peter (Macdonald Young Books, 1999)
"Forces and Motion" is part of the "Fact Files" series that aims to bring readers a wide range of up-to-date information, facts and figures on key scientific topics. Each book contains colour photographs and diagrams and a detailed text